Three new species of Neoplecostomus (Teleostei: Siluriformes: Loricariidae) from the Upper Rio Parana basin of southeastern Brazil - Roxo, Fabio F. [UNESP]; Oliveira, Claudio [UNESP]; Zawadzki, Claudio H. (Magnolia Press, 2012)
In this study, we describe three new species of the genus Neoplecostomus: N. bandeirante, from Salesopolis in the state of São Paulo, N. langeanii from Muzambinho, in the state of Minas Gerais, and N. botucatu from Botucatu, in the state of São Paulo. All of the described species are found in the Upper Rio Parana basin. The new species are different from each other and from their nominal congeners in their mitochondrial DNA sequences (COI), morphology and meristic traits, in addition to their color patterns. Morphologically, N. bandeirante can be distinguished from all congeners by the presence of moderate keels throughout the lateral series of plates and by a naked area between each mid-ventral and ventral plate that is greater in size than the length of these plates. Neoplecostomus botucatu is morphologically distinguished by a reduction of the adipose fin and the presence of dark spots that are distributed along the body. Neoplecostomus langeanii can be morphologically distinguished by the absence of hypertrophied odontodes and a swollen integument on the head, as well as by morphometric characteristics.
Keywords: catfishes; freshwater fishes; molecular identification; Neoplecostominae; Neotropical fishes; taxonomy